Transformation in Rock Harmony: An Explanatory Strategy - Christopher Doll (Gamut: Online Journal of the Music Theory Society of the Mid-Atlantic, 2009)
Explaining one musical passage by saying it is a transformed version of another is a basic strategy of analysis. In this article, I explore this strategy specifically in regard to harmonic structures in rock music. By focusing on transformations that describe obvious musical experiences (as opposed to transformations that could be considered more rational than empirical in nature), I am able to explore the usefulness of concepts such as chord substitution and musical normality as they apply to our hearings, and as they apply to the ways in which we can make sense of our hearings via a notion of transformation.
Keywords: music